PROBLEMS OF ORGANIZING THE ACCOUNT OF BIOLOGICAL ASSETS (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article examines the progress achieved in agriculture, identifies existing challenges in the accelerated transition of accounting to international standards, and outlines the essence and key provisions of IAS 41 "Agriculture." The article presents the differences between NAS and IAS in accounting for biological assets, the challenges of accounting for biological assets based on IAS 41, and solutions.